Evolution of metazoan oxygen-sensing involved a conserved divergence of VHL affinity for HIF1α and HIF2α - Daniel Tarade (Nature Portfolio, 2019)
Paralogs HIF1α and HIF2α are important modulators regulating cellular transcriptional profile following hypoxia. Here, the authors investigate evolutionary substitutions that fine tune the interaction between HIFα and their regulator VHL in the vertebrate and invertebrate lineages.